1972
DOI: 10.1104/pp.50.2.228
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Biosynthesis by Isolated Chloroplasts during Photosynthesis

Abstract: The pool sizes of the common amino acids in purified intact chloroplasts from Vicia faba L. were measured (nanomoles per milligram chlorophyll). The three amino acids present in the highest concentrations were glutamate, aspartate, and threonine. Alanine, serine, and glycine were each present at levels between 15 and 20 nanomoles per milligram chlorophyll and 13 other amino acids were detectable at levels below 10.Only aspartate, alanine, glycine, serine, threonine, and lysine became labeled during photosynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(41 citation statements)
references
References 22 publications
1
40
0
Order By: Relevance
“…Determinations which use nonaqueous techniques (1) to isolate the chloroplasts must be regarded with some caution because of the problems of cytoplasmic contamination in this type of procedure (4,9,27). Previous experiments in our laboratory (12) showed that chloroplasts isolated in aqueous media retain free amino acids but no attempt was made to estimate the amino acid concentrations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Determinations which use nonaqueous techniques (1) to isolate the chloroplasts must be regarded with some caution because of the problems of cytoplasmic contamination in this type of procedure (4,9,27). Previous experiments in our laboratory (12) showed that chloroplasts isolated in aqueous media retain free amino acids but no attempt was made to estimate the amino acid concentrations.…”
mentioning
confidence: 99%
“…Isolated plastids were broken by resuspension in ice-cold water, followed by 10 rapid strokes of a TenBroeck homogenizer and then stirred by a mechanical rotamixer until more than 95% of the plastids had lost their envelopes. The suspension ofbroken plastids was centrifuged at 3,000g for 20 min at 1 C. The supernatant was added to ethanol to a final concentration of 80%o (v/v) ethanol and recentrifuged at 3,000g for 45 min at -5 C. After reducing the volume of the supernatant to 10 ml by rotary evaporation below 40 C, it was mixed with 4 g of Dowex 50W-X8 cation exchange resin (200-400 mesh; hydrogen form) (12). The resin was washed three times with 20 ml glass-distilled H20 and the amino acid fraction removed by three washes with 4 mm NH40H.…”
mentioning
confidence: 99%
“…Interestingly, chloroplast is able to synthesize all protein forming amino acids except leucine (Kirk & Leech, 1972). Soluble amino acids that are rapidly transported to growing root and shoots are those with a high N: C ratio such as asparagine, glutamine, and arginine .…”
Section: Photosynthetic Pigmentsmentioning
confidence: 99%
“…The main pathway of glutamate is shown in Fig. 6.Glutamate is the most abundant amino acid formed by chloroplast followed by aspartate and threonine (Kirk & Leech, 1972). Glutamate is the precursor for chlorophyll synthesis in developing leaves (Yaronskaya et al, 2006), is crucial signaling molecule (Forde, 2002), is tightly regulated by light (Coschigano et al, 1998) via a phytochrome-mediated pathway (Suzuki et al, 2001) and is directly involved in the assimilation and dissimilation of ammonia (Weber & Flügge, 2002).…”
Section: Photosynthetic Pigmentsmentioning
confidence: 99%
“…;Lve since demonstrated the ability of chloroplasts to synthesize a variety of amino acids (e.g . Kirk and Leech, 1972;Leech and Murphy, 1976;Mills et al, 1980;Schulze-Seibert et al, 1984).…”
Section: Summer 1983mentioning
confidence: 99%